Optimizing circular economy practices in Nigerian construction: Effective strategies for waste reduction and resource efficiency - Hyginus C.O. Unegbu; Danjuma S. Yawas; B Dan-asabe; A.A. Alabi (BIORE Scientia Academy, 2025)
This study explores the current state of circular economy (CE) practices in the Nigerian construction industry, identifying key challenges and opportunities for their implementation. Utilizing a mixed-methods approach, data were collected from 200 survey participants and 20 key informants through structured surveys and semi-structured interviews. The quantitative data were analyzed using descriptive and inferential statistics, including regression and factor analysis, to uncover the relationships between variables and the underlying dimensions of barriers to CE adoption. The findings reveal that while there is a moderate level of awareness and implementation of CE practices, such as waste segregation and the use of recycled materials, these practices are not yet widespread. Major barriers identified include lack of awareness, high implementation costs, and insufficient regulatory support. Specifically, 75% of respondents cited lack of awareness as a significant barrier, and 80% identified high costs as a deterrent. Regression analysis indicated that awareness level, regulatory support, and company size positively influence CE practice adoption, while perceived cost has a negative impact. The study also highlights positive perceptions towards CE practices among industry professionals, with 85% of respondents recognizing their importance for the future of the construction industry. Factor analysis revealed three main dimensions of barriers: financial, awareness and education, and regulatory and policy barriers. Based on these findings, the study recommends targeted educational programs to increase awareness, financial incentives to mitigate cost barriers, and stronger regulatory frameworks to enforce sustainable practices..